2021
DOI: 10.3390/cancers13174496
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Formation and Fusion of Cancer Cells In Vitro and In Vivo

Abstract: The generation of cancer hybrid cells by intra-tumoral cell fusion opens new avenues for tumor plasticity to develop cancer stem cells with altered properties, to escape from immune surveillance, to change metastatic behavior, and to broaden drug responsiveness/resistance. Genomic instability and chromosomal rearrangements in bi- or multinucleated aneuploid cancer hybrid cells contribute to these new functions. However, the significance of cell fusion in tumorigenesis is controversial with respect to the low f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 213 publications
(400 reference statements)
0
22
0
1
Order By: Relevance
“…In addition to its putative role in carcinogenesis cell-cell fusion has been further associated with tumor progression. Indeed, a plethora of studies demonstrated that homotypic (tumor cell × tumor cell) and heterotypic (tumor cell × normal cell) fusion events could give rise to hybrids exhibiting an increased metastatic capacity, an enhanced drug resistance, or even cancer stem/initiating cell properties (for review see: [99,[166][167][168][169][170][171][172]). In any case, despite the increasing knowledge about the impact of cell-cell fusion in tumor progression only a few proteins/phospholipids and conditions have been identified so far, which trigger the hybridization of cancer cells.…”
Section: Induction Of Cell-cell Fusion By Virus-derived Fusogens and Putative Correlation To Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its putative role in carcinogenesis cell-cell fusion has been further associated with tumor progression. Indeed, a plethora of studies demonstrated that homotypic (tumor cell × tumor cell) and heterotypic (tumor cell × normal cell) fusion events could give rise to hybrids exhibiting an increased metastatic capacity, an enhanced drug resistance, or even cancer stem/initiating cell properties (for review see: [99,[166][167][168][169][170][171][172]). In any case, despite the increasing knowledge about the impact of cell-cell fusion in tumor progression only a few proteins/phospholipids and conditions have been identified so far, which trigger the hybridization of cancer cells.…”
Section: Induction Of Cell-cell Fusion By Virus-derived Fusogens and Putative Correlation To Tumorsmentioning
confidence: 99%
“…Albeit syncytin-1 was reported to improve the prognosis of breast cancer patients [65], most data from other carcinoma types rather indicated a relationship between syncyctin-1 and tumor progression [59,61,64,66]. These findings also suggested that fusion of cancer cells in general develops a more malignant phenotype with progression of metastatic lesions [16,20,22,99,167,169,170,172]. Further involvement of syncytin-1 in the fusion of two non-transformed cells undergoing a malignant conversion has not yet been reported and, hence, remains ambiguous.…”
Section: Syncytin-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative mechanisms that resemble cancer-cell fusion are mediated by cell cannibalism, entosis, and emperipolesis that form so-called cell-in-cell structures with the exchange of DNA [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Moreover, genes and mRNAs of fusion markers could be transferred by horizontal/lateral gene transfer or via extracellular vesicles, thereby altering the phenotype of recipient cells [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to post-fusion processes that are accompanied by improper segregation of chromosomes, impaired proliferation, or cell death ( Sieler et al, 2021 ). After fusion, some THCs remain multinucleated, others undergo a transition “from heterokaryon to syncarion” or a decrease in ploidy ( Hass et al, 2021 ). Although most THCs usually become more aggressive than the parental cells, cancer cell aggressiveness may also decrease after fusion ( Staroselsky et al, 1991 ).…”
Section: Tumor Hybrid Cells Formation: Factors and Mechanismsmentioning
confidence: 99%